Penentuan Kriteria Pemilihan Strategi Sistem Manufaktur Menggunakan Analytic Hierarchy Process - Apriani Soepardi; Puryani .; Mochammad Chaeron; Isti Anggraini (Jurnal Teknik Industri: Jurnal Keilmuan dan Aplikasi Teknik Industri, 2012)
This paper presents the decision making process for the selection of criteria manufacturing system using AHP. The accuracy of the selection strategy is based on many criteria that termed as agility capabilities. Several influential criteria that is used in the selection are responsiveness, product quality, product cost, operator skills, and inventory. From these criteria, manufacturing responsiveness has the highest priority weight. On these criteria, the company cast metal is required to have the agility capabilities in reduction of lead-time for product development, new product introduction, and a wide variety of products. While the criteria for product quality takes places at second priority, followed by product cost, operator skill and inventory. From agility capability priorities that must be owned by the company of cast metal, the manufacturing system according to the characteristics of the organization and be able to respond appropriately to environmental changes is lean manufacturing system.